2016
DOI: 10.1038/srep23402
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of Liesegang-type pattern formation in a gaseous system

Abstract: Liesegang pattern formations are widely spread in nature. In spite of a comparably simple experimental setup under laboratory conditions, a variety of spatio-temporal structures may arise. Presumably because of easier control of the experimental conditions, Liesegang pattern formation was mainly studied in gel systems during more than a century. Here we consider pattern formation in a gas phase, where beautiful but highly complex reaction-diffusion-convection dynamics are uncovered by means of a specific laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The Liesegang phenomenon is a periodic distribution of the precipitate discovered in diffusion-limited systems in an experimental setup in which the outer electrolytes diffuse into a hydrogel containing the homogeneously distributed inner electrolyte. , Over the past century, the phenomenon has been intensively studied to understand and control the periodicity of precipitates. Early studies were mainly concentrated on the empirical regularities of the patterns in terms of the macroscopic quantities, such as the position, the formation time of the precipitation zones, and their widths . Theories including prenucleation and postnucleation theories were proposed to explain band formation based on the interaction between the reaction and diffusion, , and numerical simulations were attempted to exquisitely interpret the pattern formation.…”
Section: Introductionmentioning
confidence: 99%
“…The Liesegang phenomenon is a periodic distribution of the precipitate discovered in diffusion-limited systems in an experimental setup in which the outer electrolytes diffuse into a hydrogel containing the homogeneously distributed inner electrolyte. , Over the past century, the phenomenon has been intensively studied to understand and control the periodicity of precipitates. Early studies were mainly concentrated on the empirical regularities of the patterns in terms of the macroscopic quantities, such as the position, the formation time of the precipitation zones, and their widths . Theories including prenucleation and postnucleation theories were proposed to explain band formation based on the interaction between the reaction and diffusion, , and numerical simulations were attempted to exquisitely interpret the pattern formation.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of patterns is a transient nonequilibrium process driven mainly by reaction–diffusion. Since their discovery more than a century ago, LPs are one of the most studied patterns due to their wide occurrence in nature, and because of the straightforward monitoring of various chemical systems leading to these patterns in gel media. To control and model LP formation, parameters affecting the formation of LPs such as the concentrations of reagents, the gel concentrations, impurities in the gels, the degree of cross‐linking in the gels, the pH of the media, electric fields, and microwave radiation have been investigated.…”
mentioning
confidence: 99%
“…2 In the past decade, the research of these reaction−diffusion systems shifted toward the pattern design using other types of building blocks such as charged nanoparticles 14,15 and gas-phase compounds in aerogels. 16,17 Recently, it has been demonstrated that the components of the zeolitic imidazolate framework-8 (ZIF-8), zinc ions and 2methylimidazole (2-Met) molecules, in a gelled medium generated spatially continuous and periodic spatial appearance of ZIF-8 crystals with increasing size. 18,19 ZIFs are a special class of metal−organic frameworks (MOFs) that are topologically isomorphic with zeolites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The phenomenon has several hallmarks such as the distance between two consecutive bands and the width of the precipitation zones increasing with the band number. , The last 120 years of research on periodic precipitation have been focused on the chemical systems comprising hydrated (usually inorganic) ions . In the past decade, the research of these reaction–diffusion systems shifted toward the pattern design using other types of building blocks such as charged nanoparticles , and gas-phase compounds in aerogels. , Recently, it has been demonstrated that the components of the zeolitic imidazolate framework-8 (ZIF-8), zinc ions and 2-methylimidazole (2-Met) molecules, in a gelled medium generated spatially continuous and periodic spatial appearance of ZIF-8 crystals with increasing size. , ZIFs are a special class of metal–organic frameworks (MOFs) that are topologically isomorphic with zeolites. These materials have unique physical (e.g., great surface area and thermal stability) and chemical (e.g., significant transition metal containment) properties, and they are widely used in gas storage and separation, chromatography, electronics, organic chemical catalysts, and targeted drug delivery. Therefore, the development of any novel synthesis methods plays a central role in the research of MOFs.…”
Section: Introductionmentioning
confidence: 99%